Réponse des élèves de la classe XI SMA Negeri 8 Semarang à l'utilisation de Quizizz comme média d'évaluation de l’apprentissage du français - Anitdhea Chandra Ivada; Aisyiah Al Adawiyah (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
This research was conducted to provide the experience of students in class XI IPS 3 of SMA Negeri 8 Semarang in evaluating French language learning using Quizizz since it was found that the evaluation tools used by teachers were less varied. The purpose of this study is to describe student responses to cognitive, affective, and conative components, and to determine the evaluation results obtained by students using Quizizz evaluation media. This research is descriptive research using a qualitative approach. The data collection techniques used are questionnaires, tests, and documentation during French language learning. The data analysis techniques used are data analysis techniques, data reduction, data presentation, and conclusion. In determining the data analysis of student evaluation results, researchers use tests/quizzes through Quizizz. After analysis, the results showed that students' responses to the cognitive component obtained a percentage of 80.6%, the affective component of 68.05%, and the conative component of 68.7%, which can be concluded that the three components are included in the strong category. Then the results of the analysis of the results of student evaluation using Quizizz are included in the high category because the average score is 94.16 on the Saluer material and 93.5 on the Se Présenter et Présenter material.